Peningkatan Kompetensi Pedagogik Guru dalam Menyusun RPP Melalui Bimbingan Kelompok di Sekolah Binaan SD Negeri 86/III Cupak Semester Ganjil Tahun Ajaran 2021/2022 - Mat Sujarti (Departement of Mathematics Education, 2021)
This study aims to obtain data/information and discuss how to increase teacher pedagogical competence in preparing lesson plans through group guidance at SD Negeri 86/III Cupak Odd Semester 2021/2022 academic year. This type of research is School Action Research (PTS). This research was conducted at SD Negeri 86/III Cupak, Danau Kerinci District, Kerinci Regency, Jambi Province. SD Negeri 86/III Cupak is one of the schools that the author assisted in this academic year. The research was conducted in the odd semester of the 2021/2022 school year. The subjects in this study were teachers of SD Negeri 86/III III Cupak, totaling 5 people. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Data collection techniques in this study used instrument sheets, observation and documentation. The collected data were analyzed using the percentage formula. The results showed that there was an increase in teacher pedagogical competence in preparing lesson plans through group guidance at target schools at SD Negeri 86/III Cupak Odd Semesters for the 2021/2022 academic year starting from the pre-cycle, cycle I and cycle II.